KEEFEKTIFAN MODEL PEMBELAJARAN WORD SQUARE BERBANTU MEDIA PUZZLE PADA MATA PELAJARAN IPS SD - Ibnatul Izzati; Choirul Huda; Qoriati Mushafanah (Universitas Muhammadiyah Surakarta, 2017)
The problems of this research was: how the effectiveness of Word Square learning model supported by Puzzle media to improve learning outcome of Social subject of third grade at State Elementary School of Wonopringgo 01 (SDN 01 Wonopringgo). The type of this research was True Experiment Design with type of pretest-posttest control group design one kind of treatment. The samples were taken from students of the third grade of A SDN 01 Wonopringgo in the academic year 2016/2017. The data in this study was obtained through tests and documentation. Experimental research on the third grade of A which was given Word Square learning model supported by Puzzle media and the third grade of B was not given Word Square learning model supported by Puzzle media. Posttest results showed that the percentage of posttest grade of the experimental class was 95% of students expressed thoroughly, while the control class is 70%, and based on t test one-party analysis obtained ttest ttable = 3,100816112 1.72. Thus, it could be concluded that the learning with Word Square model supported by Puzzle media was effective against student learning outcomes in Social subjects (IPS) the third grade at SDN 01 Wonopringgo Pekalongan.